A Nationwide Assessment of Hypertension Among the Adult Population in Bangladesh. (June 2015) - Jesmin, Subrina; Rahman, Md. Arifur; Islam, Md. Majedul; Zaedi, Sohel; Hasan, Ammar Shaker Hamed; Habib, AKM Ahsan; Khatun, Tanzila; Sultana, Sayeeda Nusrat; Yamaguchi, Naoto; Okazaki, Osamu; Kawano, Satoru; Iwashima, Yoshio
Abstract : Objective: To evaluate the prevalence, awareness, treatment and control of hypertension among elderly individuals in Bangladesh. Method: Sociodemographic and anthropometric data and data on blood pressure were obtained for 7839 adults aged 35 years or more from the biomarker sample of the 2011 Bangladesh Demographic and Health Survey (DHS), which was a nationally representative survey with a stratified, multistage, cluster sampling design. Blood pressure values considered normal are less than 120 mmHg for SBP and less than 80 mmHg for DBP. An SBP value of 120–139 mmHg or a DBP value of 80–89 mmHg is classified as prehypertension. Findings: Overall, 73 percent of men and women age 35 and older had their blood pressure measured prior to the survey, and 27 percent had never had their blood pressure measured in their life. Overall prevalence of hypertension – defined by systolic blood pressure ≥140 and/or diastolic blood pressure ≥90 or reporting history of hypertension – was found to be 32% in Bangladeshi adult women and 19% in adult men. An additional around 28 percent of women and men are pre-hypertensive. Higher rate of hypertension is seen in urban population than in rural population. Both for men and women, highest prevalence of hypertension is seen in Khulna division. 15.9% of survey participant were told by a doctor having high blood pressure. Hypertension has significant association with age, BMI, educational level, working status, geographical region, wealth status, presence of diabetes. In Bangladeshi population, we did not find a significant association with hypertension and smoking. Forty-five percent of women and 57 percent of men are not aware that they have elevated blood pressure. Eleven percent of women and 8 percent of men are aware of their hypertension, but are not treating it. Forty-five percent of women and 36 percent of men with hypertension are taking medication for their condition, but over half of them have not controlled their blood pressure to normal levels. Only 20 percent of women and 16 percent of men with hypertension are taking medication and have their blood pressure under control. Among hypertensive subjects, 25% women and 20% men are aware of their condition, are taking medication to lower the blood pressure, but are unsuccessful in controlling the elevated blood pressure. Conclusion: Our findings emphasize the need to implement effective and low cost management regimens based on absolute levels of cardiovascular risk appropriate for the economic context. From a public health perspective, the only sustainable approach to the high prevalence of hypertension in Bangladesh is through a strategy to reduce the average blood pressure in the population.